Pari Paine Nanabaya Geeta - Manorama Biswal Mohapatra (Pritam Prakashan Bhubaneswar Odisha, 2017)
The book is related to children's literature
Keywords: Odia; Pari Paine Nanabaya Geeta; Children Literature; Odia; Odia